Effects of Incorporation of Different Forms of Curdlan Gels on the Gelling Properties and in Vitro Digestibility of Myofibrillar Protein Gels - Yining XU; Chuan’ai CAO; Baohua KONG; Xiufang XIA; Qian CHEN; Hongwei ZHANG; Qian LIU (Shipin gongye ke-ji, 2024)
The effects of the addition of curdlan gel with two different forms, thermal reversible curdlan gum (TRC) and thermal irreversible curdlan gum (TIRC) on the gelling properties and in vitro digestibility of myofibrillar proteins (MP) gel were investigated. The results showed that the gel strength and water holding capacity of MP gel significantly increased with increasing TRC or TIRC concentration (P<0.05), and reached the maximum value at 0.4%, which was confirmed by dynamic rheological behavior. Meanwhile, the addition of TRC or TIRC promoted the transformation of α-helix into β-sheet, and the hydrophobic interaction and disulfide bond were the primary forces of mixed gels. The microstructures revealed that the addition of TRC or TIRC promoted the formation of the dense and uniform protein network structure. However, the modes of interactions between TRC or TIRC and MP induced the different patterns for the gel formation, resulting in the differences in the microstructure of MP gels. In addition, the addition of TRC or TIRC inhibited protein hydrolysis into small peptides and amino acids, which significantly decreased in vitro protein digestibility (P<0.05). Especially when the supplemental level was 0.3% (w/w), the digestibility was reduced from 77.53% to 71.66%. However, no significant effect on the in vitro digestibility of MP gels was observed for each addition form of curdlan (P>0.05). Therefore, this study provides a theoretical basis for the effect of TRC or TIRC on the formation and in vitro digestion of MP gel, and lays a technical support for the application of curdlan gum in meat industry.